High Performance Mobile Communication Front-Ends in the GHz Range Using Low Loss SAW-Filters - Biebl, Erwin; Anemogiannis, Kimon; Weigel, Robert; Russer, Peter (Proc. IEEE Ultrasonics Symposium, 1991, 1991)
Novel SAW (surface acoustic wave) antenna-duplexers at 900 MHz and 1.684 GHz are presented. Each of the front ends consists of a transmitter path containing a SAW filter for noise suppression, a receiver path containing SAW filters and low-noise amplifiers, and a duplexing circuit. For the 900-MHz FDMA (frequency-division multiple access) mobile radio system the SAW filters must provide both filtering and diverging. The selectivity of the front end has been enhanced by a sophisticated design of the microstrip antenna terminal. For the European TDMA cordless telephone system, the SAW filters provide preselection and noise reduction, and pin-diode switching is used for time multiplexing. The transmitter path consists of three GaAs-FET low-noise driver amplifiers and the SAW filter. The selectivity of the receiver is enhanced by a stripline filter. The feasibility of the combination of SAW and microstrip technologies for the development of low-cost mobile radio units is demonstrated. Design, fabrication and performance of SAW microstrip front-ends in the low gigahertz range are reported
elib2cris::1512001600,biebl1991
Keywords: mobile communication systems; surface acoustic wave filters; 1.684 GHz; 900 MHz; low-noise amplifiers; microstrip antenna terminal; Radio transmitters; Receivers